Antifouling activity of Babylonia areolata - Nuraisha Hana Nadzri (2016)
A study was conducted to identify the antifouling activity of marine gastropod Babylonia areolata against two common bacteria associated with the harmful fouling activity namely Escherichia coli and Staphylococcus aureus which are a gram-negative and gram-positive bacteria respectively. The solvents used for sample extractions were of increasing polarity namely dichloromethane (DCM), ethyl acetate (EA) and methanol (MeOH). The results showed highest antifouling activity with DCM extract, moderate antifouling activity with EA extract and lowest antifouling with MeOH extract. An additional study was also conducted on antimicrobial activity of B. areolata against E. coli and S.aureus using the disc diffusion technique. Different concentrations and solvents were used for sample extraction namely DCM, EA and MeOH and the results were obtained by measuring the inhibition zone (mm). The bacterial pathogen shows maximum susceptibility inhibition zone 9.125 ± 1.920 mm for S.aureus and inhibition zone 8.875 ± 1.281 mm for E. coli against dichloromethane extracts. Low susceptibility inhibition zone 4.250 ± 4.470 mm for S.aureus and inhibition zone 3.960 ± 4.180 mm for E.coli against ethyl acetate extract and very low inhibition zone 3.833 ± 4.025 mm for Saureus against methanol extract. From these, dichloromethane was seen to be the most effective solvents used for sample extraction